Alternative Feeds for Sustainable Aquaculture: A Comprehensive Structured Review (Journal of Science, Technology and Innovation Policy, 2024)
The rising demand for sustainable aquaculture has prompted extensive research into alternative feed ingredients to replace traditional Fish Meal (FM) and Fish Oil (FO), which are linked to environmental and economic challenges. This comprehensive, structured review synthesizes recent advancements in plant and algae-based feeds, probiotics, insect meals, and other novel protein sources for aquaculture. The primary problem addressed is the need for sustainable, cost-effective, and nutritionally adequate alternatives to FM and FO to support the growing aquaculture industry while mitigating ecological impacts. Methodologically, the review encompasses a systematic analysis of peer-reviewed studies published between 2023 and 2024, evaluating the efficacy of various alternative feeds across different fish species. The flow of the study is based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Analyzing a comprehensive selection using advanced searching approaches on Scopus and Web of Science discovered (n = 34) final primary data, which were then examined. The findings were divided into three themes: 1) insect-based feeds, 2) plant and algae-based feeds, and 3) alternative protein sources. Key findings reveal that many alternative feeds, including fermented plant meals, microalgae, and insect-based ingredients, promise to maintain or enhance growth performance, improve fish health, and ensure high nutritional quality. Spirulina platensis and Schizochytrium sp. inclusion in aquafeed has been illustrated to be able to enhance growth and antioxidant capacity effectively. At the same time, Black Soldier Fly Meal (BSFM) effectively supports gut health and immune response. The review concludes that while alternative feeds offer substantial benefits, species-specific responses necessitate tailored formulations. Future research should optimize these alternative ingredients, assess long-term effects, and evaluate economic feasibility to fully integrate them into sustainable aquaculture practices. This review highlights the potential of alternative feeds to transform aquaculture into a more sustainable industry, contributing to global food security and environmental conservation.
Keywords: Alternative protein; insect-based feed; plant-algae based feeds